BABBLING STAGE CONSTRUCTION OF CHILDRENâS LANGUAGE ACQUISITION ON RURAL AREA LAMPUNG - Suhono, Suhono; Sari, Yeasy Agustina (JURNAL SMART, 2017)
AbstractÂ The aim of this research analyzed the phonological structure of babbling by children subject in eight months age on rural area Lampung. Specificaly, understanding the childrenâs language acquisition process in order to know the best way to help the children acquire their language ability maximally. The objectives of this thesis were: to describe the phonological structure of babbling which have the dominant of phonetic in babbling stage, to describe the dominant of phonetic consruction in babbling stage and the dominant phonetic on all data. This Research was qualitative research. The subject of this research was the children on different rural area Lampung. The researchers used triangulation technique and observations method in collecting the data. The result show that the dominant of phonetics construction in babbling was vowels (V), it have 30 frequency in all of data. It means that the subject more able to produce vowels in their acquisition language in babbling process.Â Â Key words: Babbling Stage, Rural Area Lampung,Childrenâs Language Acquisition